KAJIAN KURIKULUM NASIONAL DALAM PEMBELAJARAN BERBASIS TCL (TEACHER-CENTERED LEARNING) DAN SCL (STUDENT-CENTERED LEARNING) - Siti Lamusiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Curriculum plays an important and strategic role in the implementation of education as a guideline for the learning process. In Indonesia, curriculum changes generally occur every five years, although in certain conditions they may take place more quickly or over a longer period. Along with curriculum changes, learning approaches have also developed, particularly Teacher Centered Learning (TCL) and Student Centered Learning (SCL). TCL places teachers as the central figures in learning, while SCL emphasizes students’ creativity and active participation. Learning practices in Indonesia are still largely dominated by conventional TCL-based approaches, which tend to limit students’ active involvement and assume uniform abilities among learners. This study aims to analyze the development of the national curriculum, the strengths and weaknesses of TCL and SCL approaches, and their implementation in schools. The research employs a descriptive qualitative method through literature review and documentation. The findings indicate that TCL-based learning was more dominant in earlier curricula due to social, cultural, and political influences, whereas recent curricula increasingly adopt SCL, although each curriculum has its own advantages and limitations.